DESIGN, VALIDATION, AND RELIABILITY OF AN OBSERVATIONAL INSTRUMENT FOR PIVOT INFLUENCE ON TACTICAL EFFECTIVENESS IN TEAM-HANDBALL (Kinesiology, 2022)
The objective of this study was to design and validate an observational instrument to determine the influence of the pivot on tactical performance in handball. The process consisted of five stages. In the first two, a combined instrument using field formats and category repertoires was designed. The third stage consisted of validating the content by consulting a panel of highly qualified experts. The fourth phase produced reliability indices, according to Cohen's Kappa test, for both inter-observer and intra-observer performance, of over .86. Finally, the instrument was applied to a pilot study; a correlational study using Pearson's Chi2test yielded very significant dependence coefficients (p